Collaboration in the Australian and Chinese Mobile Telecommunication Markets - Zhang, Yu (Aimee). (Springer Berlin Heidelberg : Imprint: Springer, 2014)
A major objective of this book is to identify the key determinants of successful inter-firm collaborations in the telecommunications industry in Australia and China, utilizing both qualitative and quantitative research methods as complementary methodologies. The findings will provide essential information and suggestions for businesses, researchers and policy makers and shed light on how to concretely improve the performance of business collaborations. Inter-firm collaboration has become increasingly important in the global economy, as firms now rely on collaborations to access new resources, new technologies, skills, the latest market information, new markets and knowledge, to accelerate innovation, to reduce costs, and to overcome government policy barriers.